(untitled) (Annals of Medical Research, 2022)
Aim: Familial Mediterranean Fever (FMF) is an autoinflammatory illness featured by recurrent fever, arthritis, and inflammation of the serous membranes, with an autosomal recessive with recurrent attacks and is a disease that begins in childhood and lasts a lifetime. In this study, it was aimed to evaluate the correlation between disease activity and dental fear-anxiety, and dental behaviour level in children with FMF who had pain and hospital experience in early childhood. Materials and Methods: The study included 207 children ranging in age from 5 to 15 years; 93 patients with FMF and 114 healthy controls. Dental anxiety and dental fear were scored using Frankl Scale and Children’s Fear Survey Schedule-Dental Subscale (CFSS-DS). Age, sex, disease severity activity, and duration of illness were examined. Results: There was not statistical difference in dental anxiety and fear between the FMF and healthy group (p>.05). However, there was a statistically significant difference in the effect of disease severity activity on the CFSS-DS. The anxiety and fear in FMF patients was similar to healthy children, which was low. Conclusions: Dental anxiety and fear level in FMF patients was similar to healthy children, which was low. It is necessary to avoid the idea that all chronic diseases will cause dental anxiety and fear, and they should be evaluated according to the nature of the chronic disease.